1995
DOI: 10.1016/0736-5748(95)00024-b
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of GABAA receptor subunits in soma and processes of cerebellar granule cells: Effects of maturation and a GABA agonist

Abstract: Quantitative analysis of the density of alpha 1 and beta 2/3 GABAA receptor subunits was performed at the electron microscope level after indirect pre-embedding immunogold labeling with subunit-specific antibodies of rat cerebellar granule cell cultures grown for 4 or 8 days and in the presence or absence of the GABAA receptor agonist 4,5,6,7-tetrahydroisoxazolo[5,4c]pyridin-3-ol (THIP). THIP (150 microM) induced a 2-fold increase in the number of alpha 1 and beta 2/3 subunits in both cell bodies and processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…These results suggest that developmental changes in subunit composition are independent of neuronal maturation, such as settling in the normal neuronal positions, maturation of excitatory networks, and formation of inhibitory synapses with basket and stellate cells. Therefore, as reported previously using culture granule cells [3,6,7,11,15,36,49,55], α1-expression may be initiated by GABAergic innervation from Golgi cells and neighboring Purkinje cells in the central cerebellar mass. In addition, the suppression of α2 and α3 subunit-expression might be related to the GABAergic innervation.…”
Section: Regulatory Mechanisms Underlying the Expression Of The Gasupporting
confidence: 52%
“…These results suggest that developmental changes in subunit composition are independent of neuronal maturation, such as settling in the normal neuronal positions, maturation of excitatory networks, and formation of inhibitory synapses with basket and stellate cells. Therefore, as reported previously using culture granule cells [3,6,7,11,15,36,49,55], α1-expression may be initiated by GABAergic innervation from Golgi cells and neighboring Purkinje cells in the central cerebellar mass. In addition, the suppression of α2 and α3 subunit-expression might be related to the GABAergic innervation.…”
Section: Regulatory Mechanisms Underlying the Expression Of The Gasupporting
confidence: 52%
“…The mechanism for this action of GABA involves activation of preexisting GABA, receptors (Belhage et al, 1990a,b) with subsequent stimulation of formation of GABA, receptor subunit mRNA and enhancement of protein synthesis (Belhage et al, 1990a;Kim et al, 1994). It appears to involve primarily mRNA for the subunits a 1 and p2 (Kim et al, 1994) in keeping with the immunocytochemical demonstration of a large increase in the expression of these subunits after exposure of neurons to the GABAA receptor specific agonist 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP) (Hansen et al, 1991;Elster et a]., 1995).…”
Section: Consequences For Gaba Receptor Expressionmentioning
confidence: 81%
“…The mechanism for this action of GABA involves activation of preexisting GABA, receptors (Belhage et al, 1990a,b) with subsequent stimulation of formation of GABA, receptor subunit mRNA and enhancement of protein synthesis (Belhage et al, 1990a;Kim et al, 1994). It appears to involve primarily mRNA for the subunits a 1 and p2 (Kim et al, 1994) in keeping with the immunocytochemical demonstration of a large increase in the expression of these subunits after exposure of neurons to the GABAA receptor specific agonist 4,5,6,7-tetrahydroisoxazolo[5,4-c]pyridin-3-ol (THIP) (Hansen et al, 1991;Elster et a]., 1995).Although exposure of neurons to GABA or GABAA receptor agonists leads to an enhanced expression of GABAA receptors via stimulation of transcription and translation processes (Belhage et al, 1990a;Kim et al, 1994), the exact molecular mechanism remains to be established. That molecular events at the nuclear level may play an important role is underlined by the observation that polyamine biosynthesis and availability seem to be a determining factor (Abraham et al, 1994).…”
mentioning
confidence: 91%
“…Moreover, the majority of both α1 and α6 subunit proteins accumulated adjacent to the Golgi cell axon terminals. These results demonstrated that (1) GAD-positive growth cones and varicosities probably undergo a change to GABAergic terminals [26,48], (2) GABAergic synapses were massively formed during the second postnatal week [2,28,31,37], and (3) GABAergic innervation might initiate the expression of the GABA A receptor α1 and α6 subunit genes, as well as trafficking and clustering of proteins to the synaptic site [1,8,12,13,16,17,20,24,46,48,61].…”
Section: Formation and Maturation Of Gabaergic Synapses In The Cerebementioning
confidence: 96%